Mediating role of environmental commitment between green organizational identity and green innovation performance - Shakeela Mushtaq; Syed Sohaib Zubair; Mukaram Ali Khan; Sobia Khurram (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Integrating environmental goals in a company's mission and strategies not only improves the company's image as a socially responsible organization but also help in gaining a leading position of first mover advantage. In today‟s era, due to the increasing pressures towards sustainability and pro-environment policies, organizations as well as governments are making efforts in this direction. The purpose of this study is to find out the role of organizations in following green practices such as green organizational identity and green innovation performance. The current study investigates the association between green organizational identity, environmental commitment, and green innovation performance. Moreover, we also investigate how environmental commitment mediates the relationship between green organizational identity and green innovation performance. Data from manufacturing organizations is taken, these are the companies registered with WWF Green office project. Following a quantitative approach, the hypotheses developed in the light of literature are tested using structural equation modeling (SEM). Result indicates that a complementary partial mediation exists between green organizational identity, environmental commitment, and green innovation performance. Moreover, this study also aims to help in comprehending to what extent organizations are focusing on the environment and how much they value both the environment and making their operations green.
Keywords: 330; green innovation performance; environmental commitment; environmental vision; competitive advantage; green organizational identity; PLS-SEM